Global Media Sentiments on the Rohingya Crisis: A Comparative Analysis of News Articles from Ten Countries - Md. Sayeed Al-Zaman; Mohammad Harun Or Rashid (Journalism and Media)
The Rohingya crisis has been a significant issue for national and international news media, capturing their attention for an extended period and documenting various phases of the crisis. Previous research exploring the tones and portrayal of the Rohingyas in the news lacks comparative and temporal analysis of news sentiments. In this study, we aim to fill this gap by analyzing 8074 news stories on Rohingya issues published in 10 news media outlets from 10 countries between 2009 and 2023. Our computational sentiment analysis reveals that Rohingya-related news sentiments are predominantly negative and fluctuate over the years across different countries, showing little identifiable patterns. An ANOVA suggests significant variation in news sentiments among countries, with some countries exhibiting more similar sentiments than others, thus creating distinguishable groups. Some of our findings contradict previous scholarships, warranting further research and novel frameworks. Additionally, we encourage scrutiny of academic insights to address potential biases against news media’s journalistic integrity.